PENGARUH PERUBAHAN BEBAN TERHADAP KINERJA TURBIN CROSSFLOW - Hatib, Rustan; Larasakti, Andi Ade (Jurnal MEKANIKAL, 2013)
Cross water turbine is a water turbine radial flow where the flow of water in and out of the rotor through the rotor peripheral circle of the same. These turbines are often used for Power Plant Mikrohodro. For the characteristics of this turbine is strongly influenced by the opening of the blade, as well as the load on the turbine wheel each valve opening. Thus it is necessary to do research on the relationship between the load and adjust the opening round as well as the opening of the blade on each valve 500, 700 and 900. In this study, the load varied from 0.5 to 5 kg at the opening of the valves 500, 900 700dan. The research method used is a real experimental method. From this study it was found that the change in the valve opening is different loads affect the performance of cross-flow water turbines. Nt 224.6 kW biggest, biggest Nh 231.9 kW and the greatest efficiency is 96.85% obtained at the opening of the valve 900, a load of 5 kg with a rotation of 250 rpm.